Effects of the Good Behavior Game on Classwide Off-Task Behavior in a High School Basic Algebra Resource Classroom. (January 2014) - Flower, Andrea; McKenna, John; Muething, Colin S.; Bryant, Diane Pedrotty; Bryant, Brian R.
This study investigated the effects of the Good Behavior Game (GBG) on classwide off-task behavior in two ninth-grade basic algebra resource classes. Ten students with a variety of disabilities, in two classrooms, and their special education resource teacher participated in this study. A reversal design was employed, in which the special education teacher implemented GBG compared to typical practice-algebra readiness instruction. Results showed that classwide off-task behavior decreased in the GBG conditions compared to the baseline and reversal conditions. Fidelity measures indicated that the teacher implemented GBG with fidelity. Students and the teacher rated GBG favorably. Overall findings support the use of GBG for reducing classwide off-task behavior. Implications for practice and future research directions are presented.